2004
DOI: 10.1136/bjsm.2003.010306
|View full text |Cite
|
Sign up to set email alerts
|

Electrical twitch obtaining intramuscular stimulation (ETOIMS) for myofascial pain syndrome in a football player: Figure 1

Abstract: Background:Flare up of acute lower back pain associated with myofascial pain syndrome (MPS) may require various forms of treatment including activity restriction and bracing. Electrical twitch obtaining intramuscular stimulation (ETOIMS) is a promising new treatment. It involves the use of a strong monopolar electromyographic needle electrode for electrical stimulation of deep motor end plate zones in multiple muscles in order to elicit twitches.Case report:An elite American football player with MPS symptoms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…Our patient showed substantial pain relief with ETOIMS in agreement with previous studies demonstrating positive effects of needle ETOIMS in musculoskeletal pain [17,19]. In addition to the conventional methods, we utilized ultrasonogaphy for real-time guidance during the procedure, thereby ensuring safe treatment of the muscles without any damage to nearby neurovascular structures.…”
Section: Us-guided Etoims Of Scalene Muscles In a Post-stroke Patientsupporting
confidence: 73%
“…Our patient showed substantial pain relief with ETOIMS in agreement with previous studies demonstrating positive effects of needle ETOIMS in musculoskeletal pain [17,19]. In addition to the conventional methods, we utilized ultrasonogaphy for real-time guidance during the procedure, thereby ensuring safe treatment of the muscles without any damage to nearby neurovascular structures.…”
Section: Us-guided Etoims Of Scalene Muscles In a Post-stroke Patientsupporting
confidence: 73%
“…Several investigations have reported that IMES can be an effective modality on musculoskeletal pain [12][13][14][15][16]; however, few relevant studies could be found which reported effects of the IMES on myofascial trigger points [14,16]. To our knowledge, there is no study comparing the IMES and placebo approaches in patients with the MTrPs.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, this study can provide theoretical support for practical applications that use needle electrodes to deliver stimuli. These applications include intraoperative detection of motor pathways during tumor resection [47,50]; preoperative or experimental stimulation of the pudendal nerve [51] or the micturition center of the brain [6] to control bladder function; electro-acupuncture for analgesia [4,13] and peripheral nerve regeneration [16]; tinnitus suppression [19]; and intramuscular delivery of plasmid DNA [45]. Many of these applications would benefit from more accurate prediction of where the stimulation takes place: which fibers are stimulated or blocked, and what the recruitment order is.…”
Section: Discussionmentioning
confidence: 99%